2017
DOI: 10.4073/cmg.2016.1
|View full text |Cite
|
Sign up to set email alerts
|

Searching for studies: a guide to information retrieval for Campbell systematic reviews

Abstract: to use the chapter as a basis for our work, of which we are immensely grateful. Many thanks to the Canadian Council on Learning for allowing the use of the list of Sources of Grey Literature. Campbell Library Methods papers The Campbell Library Methods Series comprises three types of publications: Methods Discussion Papers New or innovative ideas currently in development in the field of methodology, these papers are intended for discussion and do not represent official Campbell policy or guidance Methods Polic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
258
0
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(270 citation statements)
references
References 49 publications
0
258
0
12
Order By: Relevance
“…It is, however, necessary to strike a balance between striving for comprehensiveness and maintaining relevance when developing a search strategy. […] The decision as to how much to invest in the search process depends on the question a review addresses and the resources that are available.” ( , p26) As a consequence, reviewers must select search systems that allow them to make the best use of their resources, that is, to retrieve the most relevant records in exchange for the least amount of time or funds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is, however, necessary to strike a balance between striving for comprehensiveness and maintaining relevance when developing a search strategy. […] The decision as to how much to invest in the search process depends on the question a review addresses and the resources that are available.” ( , p26) As a consequence, reviewers must select search systems that allow them to make the best use of their resources, that is, to retrieve the most relevant records in exchange for the least amount of time or funds.…”
Section: Introductionmentioning
confidence: 99%
“…The second and third goal of systematic reviews, reproducibility (also “replicability,” “reliability,” and “repeatability”) and transparency , require an explicit, transparent, and documented search process that allows reviewers to update or replicate a given synthesis search. “The search process needs to be documented in enough detail throughout the process to ensure that it can be reported correctly in the review, to the extent that all the searches of all the databases are reproducible.” ( , p41) Conduct and reporting guidance explicitly describe the steps necessary for a reviewer to ensure the rigorous and transparent documentation necessary to foster reproducibility. However, the functionality and capabilities of specific search systems can also influence reproducibility themselves.…”
Section: Introductionmentioning
confidence: 99%
“…This premise underpins search approaches for systematic reviews of clinical trials in human health. It is expected practice that review authors search for unpublished trials, gray literature, and studies published outside of English language sources to minimize the possibility of publication bias …”
Section: Discussionmentioning
confidence: 99%
“…The NICE methods manual has been revised to stipulate that search terms should be documented for all literature resources, including search engines and websites, since it was reviewed by Briscoe . The Campbell Collaboration guidance recommends recording the URL and date accessed of useful webpages identified by web searching for citation purposes and stipulates that the names and search strategies of all resources used to identify studies, including search engines and websites, should be reported.…”
Section: Introductionmentioning
confidence: 99%
“…Items 1 to 4 relate to the search methods and item 5—which is an additional item not mentioned in the reporting guidance in Table —relates to the search results. The date that a useful webpage was accessed, which the Cochrane Handbook and Campbell Collaboration guidance recommends documenting for citation purposes, is not included in the table, as this describes the date a URL was most recently accessed prior to the publication of a review (eg, to check that the URL is still functional) rather than the date that the search that identified the webpage was conducted. The number of included studies identified by web searching (ie, studies identified by web searching that were included in the results and conclusions of the reviews) is also not included on the table, as this detail is unrelated to the transparency and reproducibility of the search methods.…”
Section: Introductionmentioning
confidence: 99%